Pengaruh Job Crafting terhadap Work Engagement pada Pegawai Unit Pelayanan Teknis BPPD - Hasmi Havila; Agus Budiman (UNISBA Press, 2022)
Abstract. Job crafting is an effort to change made by employees to balance job demand and job resources to suit their preferences, skills and abilities (Berg, Wezesniewski and Dutton, 2010). This study aims to determine the effect of job crafting on work engagement for BPPD employees in Bandung. The theoretical concept used in this study is the theory of Tims, Bakker and Derks to explain the concept of job crafting and the theory of Schaufeli and Bakker to explain the concept of work engagement. The research method used is causality with regression analysis to explain the effect of job crafting variables on work engagement. Respondents from this study were 65 BPPD employees in the city of Bandung. The measuring instrument used is the job crafting scale based on the theoretical concepts of Tims, Bakker and Derks, and the Utrecht Work Engagement Scale (UWES 17) based on the theoretical concepts of Schaufeli and Bakker. The results of the study indicate that there is an effect of job crafting on work engagement in technical service unit employees by 36.36% (R Square = 0.364). All components of job crafting have a positive influence on work engagement with an effect of 5.75% from the dimensions of increasing structural job resources, 0.21% from the dimensions of increasing social job resources, by 3.18% from the dimensions of decreasing hindering job demands, and by 32.38% from the dimensions of increasing challenging. job demands. Keywords: Job Crafting, Work Engagement, Job Demands, Job Resource Abstrak. Job crafting merupakan upaya perubahan yang dilakukan karyawan untuk menyeimbangkan job demand dan job resources agar sesuai dengan preferensi, keterampilan dan kemampuannya (Berg, Wezesniewski dan Dutton, 2010). Penelitian bertujuan untuk mengetahui pengaruh job crafting terhadap work engagement pada pegawai BPPD di Kota Bandung. Konsep teori yang digunakan dalam penelitian ini adalah teori dari Tims, Bakker dan Derks untuk menjelaskan konsep job crafting dan teori dari Schaufeli dan Bakker untuk menjelaskan konsep work engagement. Metode penelitian yang digunakan adalah kausalitas dengan analisis regresi untuk menjelaskan pengaruh variabel job crafting terhadap work engagement. Responden dari penelitian ini sejumlah 65 pegawai BPPD di Kota Bandung. Alat ukur yang digunakan yaitu skala job crafting yang berdasarkan dari konsep teori Tims, Bakker dan Derks, serta skala Utrecht Work Engagement Scale (UWES 17) dari konsep teori Schaufeli dan Bakker. Dari hasil penelitian menunjukkan bahwa terdapat pengaruh job crafting terhadap work engagement pada pegawai unit pelayanan teknis sebesar 36.36% (R Square = 0. 364). Seluruh komponen job crafting memiliki pengaruh positif terhadap work engagement dengan pengaruh sebesar 5.75% dari dimensi increasing structural job resources, sebear 0.21% dari dimensi increasing social job resources, sebesar 3.18% dari dimensi decreasing hindering job demands, dan sebesar 32.38% dari dimensi increasing challenging job demands. Kata Kunci: Job Crafting, Work Engagement, Job Demands, Job Resource